Eco-technological and socio-economic analysis of fish farming systems in the freshwater area of Mekong Delta 1996-1997 (Cantho Univ. - College of Agriculture, 1997)
This report describes in details the present structure, functioning and the level of management of fish farming systems existing in Cantho and Vinhlong provinces. There are 3 major farming systems with fish: 1) Fish culture in ponds and/or garden canals (A). 2) Fish culture integrated with animal (with/without trees) (AC/VAC). 3) Fish culture in rice field (with/wihtout garden canals or animals) (AR/VAC-R)